Barriers to access second-trimester abortion: A case report - Ramprakash Kaswa (South African Family Practice)
Despite the implementation of the Choice on Termination of Pregnancy (CTOP) Act, many women continue to procure illegal abortions in South Africa. A lack of knowledge of the CTOP Act and poor access to legal abortion in public health facilities is a big challenge. In the scope of the CTOP Act, the termination of pregnancy is a time-restricted health service, and women presented to a health care facility in the second trimester have encounter more obstacles to access the services.